A coherence-based algorithm for noise reduction in dual-microphone applications - Yousefian, Nima; Kokkinakis, Kostas; Loizou, Philipos C. (Proceedings of the ... European Signal Processing Conference (EUSIPCO), 2010)
In this paper, we present a novel coherence-based dual-microphone noise reduction approach and show how the proposed technique can capitalize on the small microphone spacing in order to suppress coherent noise present inside a realistic reverberant environment. Listening tests with normal-hearing subjects conducted in a two-microphone array configuration, reveal that the proposed method outperforms the generalized sidelobe canceller (GSC), which is commonly used in suppressing coherent noise.